2020
DOI: 10.1007/s42452-020-03851-3
|View full text |Cite
|
Sign up to set email alerts
|

First principles study on copper and iridium co-doped SrTiO3 for shifting the optical absorption into visible region

Abstract: Density functional theory (DFT) investigation is performed to observe the opto-electronic properties of iridium and copper co-doped structure of Pristine SrTiO 3 (Cubic Perovskite). Results suggest that copper and iridium co-doped structure of SrTiO 3 has significant absorption in visible region of the spectrum, which is a result of red shift phenomenon in the wavelength range 400-750 nm observed in this structure. However, in individual copper and iridium structures the optical absorption is mainly in ultravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The STO composition is observed to present a strong absorption in the UV region, with a negligible absorption for energies inferior to 3 eV, which is in good agreement with previously reported values. 42 For the BFO system, a first absorption edge is observed near 2.9 eV (⁓430 nm), originating from the transition from O 2p (VB) to Fe 3d (CB) orbitals, which further increases in the UV region. Note that, the substituted composition presents the highest absorption in the visible light region (1.77 -3.26 eV) compared to BFO and STO, which corroborates with our experimental results (figure 5c).…”
Section: Dft Calculationsmentioning
confidence: 99%
“…The STO composition is observed to present a strong absorption in the UV region, with a negligible absorption for energies inferior to 3 eV, which is in good agreement with previously reported values. 42 For the BFO system, a first absorption edge is observed near 2.9 eV (⁓430 nm), originating from the transition from O 2p (VB) to Fe 3d (CB) orbitals, which further increases in the UV region. Note that, the substituted composition presents the highest absorption in the visible light region (1.77 -3.26 eV) compared to BFO and STO, which corroborates with our experimental results (figure 5c).…”
Section: Dft Calculationsmentioning
confidence: 99%
“…The electron conductivity of TiO 2 could be enhanced as the Ir states cross the Fermi level . First-principles calculation revealed that the absorption edge of TiO 2 could be extended toward the visible region by Ir doping, due to its distinctive electronic structure. , …”
Section: Introductionmentioning
confidence: 99%
“…16 First-principles calculation revealed that the absorption edge of TiO 2 could be extended toward the visible region by Ir doping, due to its distinctive electronic structure. 17,18 In the recent years, the activity of Ir-doped TiO 2 (Ir-TiO 2 ) has been studied for hydrogen production, 15,19 remediation of gas pollutants, 20,21 photo-electrochemical sensing, 22 carbon dioxide reduction, 23 and antimicrobial activity. 24 All these studies indicate that Ir doping is beneficial to maximize the activity of TiO 2 , through an enhanced electron−hole separation.…”
Section: Introductionmentioning
confidence: 99%